Adaptive plasmonic metasurfaces for radiative cooling and passive thermoregulation - Didari-Bader, Azadeh; Estakhri, Nooshin M.; Mohammadi Estakhri, Nasim (Frontiers in Photonics, 2023)
In this work, we investigate a class of planar photonic structures operating as passive thermoregulators. The radiative cooling process is adjusted through the incorporation of a phase change material (Vanadium Dioxide, VO2) in conjunction with a layer of transparent conductive oxide (Aluminum-doped Zinc Oxide, AZO). VO2 is known to undergo a phase transition from the “dielectric” phase to the “plasmonic” or “metallic” phase at a critical temperature close to 68 °C (Sun, Xiao, et al., 2022). In addition, AZO shows plasmonic properties at the long-wave infrared spectrum, which, combined with VO2, provides a rich platform to achieve low reflections across the atmospheric transparency window, as demanded in radiative cooling applications, while also maintaining a compact size. Using numerical analysis, we study two classes of patterned and non-patterned compact multilayer metal-dielectric-metal metasurfaces, aiming to maximize the overall absorption in the first atmospheric transparency window (8-13 µm) while maintaining a high reflection across the solar spectrum (0.3-2.5µm). Surfaces are initially designed based on a round of coarse optimization and further improved through analyzing the impact of geometric parameters such as size and periodicity of the metasurface elements. Our findings are relevant to applications in thermal regulation systems and passive radiative cooling of high-temperature devices, such as electronic elements.